SURVEY OF THE ATTITUDES OF GENERAL PRACTITIONERS AND PATIENTS ABOUT DISCUSSING RESUSCITATION. Issue 2 (1st June 2013) - Lim, I; Silvester, W
Abstract : Background: When confronted with acutely unwell, elderly patients, doctors often have limited knowledge about the patient's wishes for resuscitation. Providing inappropriate resuscitation causes patients to suffer, places unnecessary strain on their families and is a poor use of healthcare resources. Is the general practitioner (GP) well placed to discuss these issues with patients? Aim: To survey the practice and attitudes of GPs and patients to discussing resuscitation and identify strategies to encourage such discussion. Methods: From 18 April 2011 to 26 June 2011 Victorian GPs were surveyed anonymously through GP Divisions of Victoria and patients attending Ararat Medical Clinic aged over 65 were surveyed anonymously. Results: 90 GPs responded. Identified incentives to discuss resuscitation included: 'knowledge that my patient wanted discussion' 79%, 'incorporation into management plan' 71%, 'discussion guidelines available' 42%, 'medicare item number' 34%. Very few felt uncomfortable about the discussion or 'not my duty'. Of 97 patients, 63% did not know what a resuscitation order was but 70% would like their GP to discuss it with them and 84% would be comfortable talking about it with family. Discussion: Although the majority of GPs do not discuss resuscitation frequently with their patients, for various reasons, there are opportunities, through perceived 'incentives', to improve the discussion rate. The majority of their patients are keen and comfortable to have this discussion. Conclusion: The majority of GPs believe that it is their responsibility, and the majority of patients that it is their wish, to discuss resuscitation. There are realistic opportunities to increase the discussion rate.